2006
DOI: 10.1038/sj.emboj.7601107
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli acid resistance: pH-sensing, activation by chloride and autoinhibition in GadB

Abstract: Escherichia coli and other enterobacteria exploit the H þ -consuming reaction catalysed by glutamate decarboxylase to survive the stomach acidity before reaching the intestine. Here we show that chloride, extremely abundant in gastric secretions, is an allosteric activator producing a 10-fold increase in the decarboxylase activity at pH 5.6. Cooperativity and sensitivity to chloride were lost when the N-terminal 14 residues, involved in the formation of two triple-helix bundles, were deleted by mutagenesis. X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(109 citation statements)
references
References 43 publications
2
105
0
1
Order By: Relevance
“…Of considerable importance is the dramatic up-regulation (65-fold) of the GABA/glutamate antiporter GadC, which facilitates both utilization of glutamate as a carbon source and the generation of a pH gradient via uptake of glutamate and export of GABA. The reaction catalyzed by the GadB glutamate decarboxylase enzyme, encoded by the most dramatically up-regulated gene in cydB cells, is marked with a dashed line because this process is poorly catalyzed above pH 4.5 (41,42). These observations are consistent with the hypothesis that E. coli may uncouple catabolism from ATP synthesis by shutting down NADH synthesis, consuming NADH and ubiquinol electroneutrally, and translocating protons via GABA/glutamate antiport.…”
Section: Loss Of Cydb Causes Diminished Respirationsupporting
confidence: 77%
See 2 more Smart Citations
“…Of considerable importance is the dramatic up-regulation (65-fold) of the GABA/glutamate antiporter GadC, which facilitates both utilization of glutamate as a carbon source and the generation of a pH gradient via uptake of glutamate and export of GABA. The reaction catalyzed by the GadB glutamate decarboxylase enzyme, encoded by the most dramatically up-regulated gene in cydB cells, is marked with a dashed line because this process is poorly catalyzed above pH 4.5 (41,42). These observations are consistent with the hypothesis that E. coli may uncouple catabolism from ATP synthesis by shutting down NADH synthesis, consuming NADH and ubiquinol electroneutrally, and translocating protons via GABA/glutamate antiport.…”
Section: Loss Of Cydb Causes Diminished Respirationsupporting
confidence: 77%
“…5). Under conditions of low internal pH, the highly up-regulated GadB glutamate decarboxylase will become active (41,42) and catalyze the synthesis of GABA, which can be used by GadC for the removal of protons from the cell. However, under the experimental conditions for the current microarray data, the internal pH of both cydB and wild type cells is slightly alkaline (supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In LAB and E. coli, GABA production is among the most important mechanisms for achieving acid resistance. [26][27][28] Since Lb. paracasei increases acidity via growth, it has been suggested that it produces GABA in order to increase the pH of the growth medium.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, pXO1-118 crystallized in sodium chloride, whereas pXO2-61 required the presence of 1.0 M sodium iodide. Iodide is a strongly chaotropic agent that disfavors complex formation and increases the solubility of hydrophobic moieties (38), consistent with the expulsion of fatty acid from the protein. The higher pH required for crystal growth of pXO2-61 (pH 7.5 versus 5.4) may also disfavor binding (see below).…”
Section: Crystal and Solution Structures Of Pxo1-118 And Pxo2-61-mentioning
confidence: 99%